Sedentary lifestyle as a leading factor in cardiovascular disease in the Honorato Vázquez community in Ecuador - Orellana, María M.; Navarrete, Manuel A.; Sabando, Marcos G.; Quinteros, Julio L.; Rivadeneira, Elián J.; Román, Víctor V.; Rodríguez, Orelvis (Revista Gregoriana de Ciencias de la Salud, 2025)
Sedentary behavior is a key factor in the development of cardiovascular diseases (CVD), posing an increasing threat to public health. This study aimed to analyze individual, social, and environmental factors influencing the adoption of a sedentary lifestyle in the Honorato Vásquez parish, Santana canton (Manabí, Ecuador). A descriptive study was conducted with 144 participants aged 30 years or older, classified by physical activity levels. Structured surveys assessed knowledge, habits, and conditions related to a sedentary lifestyle. Results revealed that 70% of respondents spent over 10 hours a day sitting, and 60% experienced symptoms like joint pain without physical exertion. Although 80% were aware of the risks and expressed willingness to change, barriers such as lack of time and inadequate public spaces remain. It is concluded that sedentary behavior is a prevalent risk factor that is exacerbated by social and environmental conditions. Community-based strategies are urgently needed to promote active lifestyles and reduce CVD incidence.